DISTINCTIVE FEATURES OF MENTAL EDUCATION FOR PRESCHOOL CHILDREN - Zoirova Makharram (Web of Journals Publishing, 2024)
This article provides information on the peculiarities of mental education for preschool children.
Keywords: preschool age, children, mental, educational, specific features.